Effects of obesity and acute resistance exercise on skeletal muscle angiogenic communication pathways. Issue 8 (31st May 2022) - Garner, Ron T.; Weiss, Jessica A.; Nie, Yaohui; Sullivan, Brian P.; Kargl, Christopher K.; Drohan, Cathal J.; Kuang, Shihuan; Stout, Julianne; Gavin, Timothy P.
Abstract : New Findings: What is the central question of this study? Do obesity and acute resistance exercise alter the regulation of muscle intercellular communication pathways consistent with inadequate compensatory angiogenesis in response to muscle loading present in individuals with obesity? What is the main finding and its importance? Obesity is associated with differences in both pro‐ and anti‐angiogenic signalling consistent with lower muscle capillarization. Acute resistance exercise increases the release of skeletal muscle small extracellular vesicles independent of body mass. These results identify new cellular factors associated with impaired angiogenesis in obesity and the positive effects of acute resistance exercise in lean and obese skeletal muscle. Abstract: Obesity (OB) impairs cell‐to‐cell communication signalling. Small extracellular vesicles (EVs), which include exosomes, are released by skeletal muscle and participate in cell‐to‐cell communication, including the regulation of angiogenesis. Resistance exercise (REx) increases muscle fibre size and capillarization. Although obesity increases muscle fibre size, there is an inadequate increase in capillarization such that capillary density is reduced. It was hypothesized that REx‐induced angiogenic signalling and EV biogenesis would be lower with obesity. Sedentary lean (LN) and OB subjects ( n  = 8 per group) performed three sets of single‐leg knee‐extension REx at 80% of maximum. Muscle biopsies were obtained at rest, 15 min and 3 h postexercise and analysed for angiogenic and EV biogenesis mRNA and protein. In OB subjects, muscle fibre size was ∼20% greater and capillary density with type II fibres ∼25% lower compared with LN subjects ( P  < 0.001). In response to REx, the increase in VEGF mRNA (pro‐angiogenic) was similar (3‐fold) between groups, while thrombospondin‐1 ( TSP‐1 ) mRNA (anti‐angiogenic) increased ∼2.5‐fold in OB subjects only ( P  = 0.010). miR‐130a (pro‐angiogenic) was ∼1.4‐fold ( P  = 0.011) and miR‐503 (anti‐angiogenic) ∼1.8‐fold ( P  = 0.017) greater in OB compared with LN subjects at all time points. In both groups, acute REx decreased the EV surface protein Alix by ∼50%, consistent with the release of exosomes ( P  = 0.016). Acute REx appears to induce the release of skeletal muscle small EVs independent of body mass. However, with obesity there is predominantly impaired angiogenic signalling, consistent with inadequate angiogenesis in response to basal muscle hypertrophy.